How fdhF Deletion Affects Ion Transport and ATPase Activity in E. coli? (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Formate dehydrogenase-H plays a key role in anaerobic metabolism, particularly in formate metabolism during fermentation. To assess its glucose-dependent role, proton (JH⁺) and potassium (JK⁺) fluxes, along with FOF1-ATPase activity, were examined in wild-type and fdhF mutant grown under low (2 g L⁻¹) and high (8 g L⁻¹) glucose. When cells were grown in the presence of low glucose and during assays similar amount was added mutant showed 40% higher JH⁺ but 30% lower FOF1-conditioned flux, consistent with a 20% reduction in ATPase activity upon potassium supplementation, but there were no differences when extra formate, or potassium and formate together were supplemented. At the same time total JK+ was lower compared to wild type, meanwhile DCCD does not affect the flux. Under high glucose, mutants displayed a 50% increase in total and DCCD-sensitive JH⁺ fluxes, a 35% decrease in JK⁺, and a 50% drop in FOF1-conditioned flux. When cells were grown in a presence of high glucose and during assays similar amount was supplemented total JH+ was similar in mutant and wild type, meanwhile DCCD-sensitive flux decreased by 25-35%, conversely total JK+ increased by 35% and with DCCD potassium outflux was observed. Potassium had no effect on ATPase activity, but formate increased it by 25%. These findings suggest that under low glucose, accumulated formate stimulates proton efflux while inhibiting ATPase, whereas under high glucose, formate regulates ATPase via potassium, highlighting a glucose-dependent shift in formate’s control of membrane bioenergetics.
Keywords: formate dehydrogenase H; FOF1-ATPase; JH⁺; JK⁺; glucose concentration